PENGARUH BAHAN AJAR HANDOUT TERHADAP PENINGKATAN KETERAMPILAN PROSES PESERTA DIDIK KELAS VII PADA MATERI EKOSISTEM DI SMP NEGERI 3 BATAM TAHUN PELAJARAN 2012/2013 - Hendra Kirana; Nurhaty Purnama Sari; Rahmi Rahmi (SIMBIOSA, 2013)
This research has been carried out in SMP Negeri 3 Batam is located on the street Kartini II Sekupang, Batam. While time research has been carried out in the second half Academic Year 2012/2013, from March to May of 2013. This study aims to prove the influence of handout materials to increase the skills of the students of class VII on ecosystem material in SMP Negeri 3 Batam Academic Year 2012/2013. Handout is a concise study materials are sourced from some of the literature relevant to the basic competencies and subject matter that is taught to students given by teachers to students to achieve learning goals. While the process skills of learners is the ability to collect information, manage information and communicate the results of using information to achieve learning objectives both on cognitive aspects or psychomotor aspects. Research using quasi-experimental methods. Affordable population is all students of class VII with the target population VII1 class as a class experiment with a treatment using learning materials and classroom handouts VII4 as classroom control by providing a treatment study using conventional materials. Cluster sampling using random sampling techniques. Research data is data science learning outcomes Biological processes in the form of skills, which is obtained using the test results to learn the instrument objective test (multiple choice). Data were analyzed with descriptive statistical analysis techniques and inferential statistical analysis using the t test of the parties at significant level (α.) = 0.05. Based on the analysis of the calculation results obtained descriptive study of students from the class experiment with a mean value of 83.6 and a mean value of 80 control classes. While the calculation of inferential analysis of testing hypotheses derived tcount 2,081 and the value ttable 2, 018. Thus the value of t greater than ttable which means a hypothetical zero (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Overall it can be concluded the research, analysis of the calculation of descriptive and inferential analysis proves that there are significant handout materials to increase the skills of the students of class VII on ecosystem material in SMP Negeri 3 Batam Academic Year 2012/2013.